Development of Educational Communication Path of Journalism in Colleges and Universities in the Era of Mobile Communication. (28th January 2022) - Xu, Xiaoman; Liu, Chunxia
Abstract : The development of journalism has a huge impact on mobile communication technology and media ecology. Especially in terms of information dissemination, it not only allows people to better obtain the content they are interested in but also provides media workers with more ways to understand their own needs, meet the needs of audiences, and enhance competitiveness. Therefore, in order to enhance the development space of the journalism major, this article studies the communication development path of this major in colleges and universities in the era of mobile communications. This article mainly uses case analysis method, data method, and investigation method to study the development of journalism education in colleges and universities. The survey results show that 21 people believe that the authenticity of news is an indispensable item in teaching. Therefore, the education and communication development of journalism majors in colleges and universities cannot ignore the principle of authenticity. There are 18 people who think it is necessary to tie their majors with the Internet, indicating that colleges and universities can use the Internet platform to teach journalism.